Handbook process and procedures for investment profects in areas outside industrial and economic zones in Binh Dinh province : (Lao động, 2011)
This handbook was developed as part of an investment climate advisory services project between IFC, a member of the World Bank Group, and Binh Dinh provincial people's committee. This technical cooperation initiative concentrates on strengthening inter-agency coordination and simplification of the administrative process and process and proceduces for investment and construction in areas uotside industrial parks in Binh Dinh province.